Application Of Technology Acceptance Model (TAM) To Analyze Alfagift Application Acceptance In Sukabumi Regency - Sinta Desiana; Cecep Warman (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the acceptance of the Alfagift application in Sukabumi Regency using the Technology Acceptance Model (TAM) developed by Davis (1989). This quantitative research involved 100 application users as respondents, with data collected through a Google Form–based questionnaire and analyzed using SmartPLS 4 to examine validity, reliability, and structural relationships among the main variables: Perceived Usefulness (PU), Perceived Ease of Use (PEU), Attitude Toward Using (ATU), Behavioral Intention to Use (BI), and Actual System Use (AU). The descriptive analysis results indicate that the mean scores of all variables exceed 4.30 on a 5-point Likert scale, with PEU showing the highest mean value (4.56), suggesting that perceived ease of use is the most dominant factor in application acceptance. Convergent validity and reliability tests (Cronbach's Alpha > 0.7; Composite Reliability > 0.7; AVE > 0.5) confirm the adequacy of the measurement instrument, although one indicator (PEU3) was found to be invalid. Hypothesis testing demonstrates that PU and PEU have positive and significant effects on ATU and BI, and BI significantly influences AU, in line with the classical TAM framework. Although the R-square values ​​for BI (0.431) and AU (0.279) indicate weak to moderate explanatory power, the findings provide empirical contributions to the development of Alfamart's omnichannel retailing strategies, the enhancement of digital literacy in Sukabumi, and the body of TAM literature on local mobile commerce applications. Practical implications include optimizing intuitive features to improve user adoption.